On the size and orientation effect in additive manufactured Ti-6Al-4V. (15th January 2020) - Barba, D.; Alabort, C.; Tang, Y.T.; Viscasillas, M.J.; Reed, R.C.; Alabort, E.
Abstract: In this work, the influence of the specimen size and orientation on the strength and ductility of additive manufactured Ti-6Al-4V is analysed and rationalised in a complete framework. First, the mechanical properties are addressed – as a function of surface-type, orientation, and size. Our results show systematic strengthening and a drastic drop in ductility as the material section is reduced. These changes are rationalised and linked to changes in microstructure, chemistry, and surface quality. Strengthening is due to combined changes in α-lath thickness, oxygen enrichment, and prior-β grain size. The microstructural changes are due to the differences in the ratio between contouring and hatching laser strategies as the sample size decreases. Changes in the chemical composition is due to an increase in the surface-to-volume ratio as the sample size decreases. Lost of ductility is due to poor surface quality – smaller sections show rougher surfaces – and grain orientations. Finally, these findings are used to develop a set of conceptual design maps of strength and ductility as a function of the component type, thickness, and orientation. Graphical abstract: Image 1 Highlights: The specimen size and orientation effect on strength and ductility of additive manufactured Ti-6Al-4V is rationalised. Our results show systematic strengthening and a drastic drop in ductility as the material section is reduced. These changes are rationalised and linked to changes in microstructure, chemistry, and surface quality. Strengthening is due to combined changes in α-lath thickness, oxygen enrichment, and prior-β grain size.